Petrology and structure of precambrian crystalline and tertiary igneous rocks, Manhattan District, Larimer County, Colorado - Samuelson, Donald Robert, author; McCallum, M. E. (Malcolm E.), 1934-, advisor; Campbell, J. A., committee member; Warren, C. G., committee member (Colorado State University. Libraries, 1971)
The Manhattan district is located in the northwest quarter of the Rustic quadrangle about 30 miles northwest of Fort Collins, Colorado, and includes approximately five square miles of primarily Precambrian terrane. Biotite gneiss, hornblende gneiss, and amphibolite, the oldest rocks in the area, have been metamorphosed to the sillimanite-almandine-orthoclase subfacies of the amphibolite facies. The metamorphic rocks have been intruded by Log Cabin granite which comprises the majority of the rock in the area. Granite shows evidence of forceful, but not very disruptive, intrusion. Inhomogeneity in the granite suggests that it may not have been completely molten when intruded or that the magma may have been locally altered by assimilation. Pegmatite and foliated granite are considered to be phases of the Log Cabin granite. A period of cataclasis in late Precambrian produced several shear zones in the granite. Degree of cataclasis varies and shear zone rocks range from cataclasite to mylonite. More intensely sheared zones have been rehealed with quartz and epidote. Brecciated structure in shear zones suggests at least two periods of shearing. Uplift of the area during formation of the Ancestral Rockies or during the Laramide orogeny may have reactivated the shear zones. An episode of mineralization, probably in early Tertiary time, produced minor urqnium mineralization in a few shear zones and along minor faults in the general area. In mid- Tertiary time numerous porphyritic dikes of rhyolite, rhyodacite, and hornblende rhyodacite were emplaced primarily along joint planes in granite. Variations in chemistry and mineralogy suggest that the intrusives were formed either from a differentiating magma, from slightly different magmas, or from different fractions of the same magma modified by assimilation. Ore solutions probably associated with Tertiary magma produced pyrite, chalcopyrite, minor gold, silver, and copper mineralization in the Manhattan district. Formation of a Tertiary erosion surface apparently was accompanied by the secondary enrichment of gold on the surface above low grade primary gold ore deposits. Near the end of Tertiary time a period of rapid down cutting was inaugurated. Although the relatively flat erosion surface is still present in the northern third of the Manhattan district, the southern portion of the area has been well dissected. Granite joints, although fairly well developed, have had little influence on development of the general topography.
Keywords: Geology, Stratigraphic -- Precambrian; Geology -- Colorado -- Larimer County